Reasons, associated factors, and attitudes toward breastfeeding mothers’ use of complementary medicine products: a study from Türkiye - Demet Deniz Bilgin; Nalan Karabayir; Hatice Bilge Çetinkaya; Aybüke Kacir; Özlem Öçal; Mine Başibüyük; Övgü Büke (International Breastfeeding Journal)
Abstract Background The use of Complementary Medicine Products (CMPs) has been increasing worldwide, including among breastfeeding mothers. This study aims to investigate the reasons and associated factors of CMP use among breastfeeding mothers in Turkey, alongside their attitudes and experiences. Methods A descriptive cross-sectional study was conducted using a self-administered, anonymous online survey between 17 December 2023 and 17 March 2024. Women from diverse regions across Türkiye, aged 18 years or older, with a child aged 36 months or younger, who were currently breastfeeding or had breastfed, were invited to participate in the survey. Results Among 445 mothers who completed the survey, 334 (75.1%) reported using at least one CMP during breastfeeding, with vitamin D, iron supplements, and fennel being the most frequently used. Educational level, employment status, and being a health worker were found to be factors associated with CMP use during breastfeeding, with those having university or higher education, being employed, or working in healthcare showing higher usage rates. The most common reasons for CMP use were “staying healthy” (60.2%) and “supporting immunity” (59.3%). While 91.9% of mothers perceived at least one CMP they used as beneficial, 14.4% of mothers using CMPs experienced adverse effects with at least one product. Safety perceptions of mothers who used CMP varied, with 45.8% believing CMPs were generally safe during breastfeeding. Among CMP users, doctors were chosen as the most trusted (n = 310, 92.8%) information source. A majority of mothers (85.6%) reported that they would like to receive more information about the safety and effectiveness of CMPs. Conclusions Breastfeeding mothers often use CMPs to stay healthy and support immunity. While healthcare providers are the most trusted source of information, many women get advice from family, friends, or herbalists, and some use CMPs without any recommendations. This underscores the importance of healthcare providers’ role in guiding mothers on the safe and informed use of both prescribed and self-prescribed CMPs.